Evaluation of lipidomic change in goat sperm after cryopreservation - Xu, Bingbing; Wang, Ruijun; Wang, Zhiying; Liu, Hongfu; Wang, Zhen; Zhang, Weihang; Zhang, Yanjun; Su, Rui; Liu, Zhihong; Liu, Yongbin; Li, Jinquan; Zhang, Jiaxin (Frontiers in Veterinary Science, 2022)
Semen cryopreservation is widely used for conservation of animal genetic resources and the utilization of superior patrilineal genes through artificial insemination, but semen from different goat individuals shows significant differences in semen quality after a unified freeze-thawing procedure. The current study performed a uniform freeze-thawing procedure using ejaculates from twenty goats, and evaluated sperm motion parameters, plasma membrane integrity and acrosome integrity after thawing. According to the characteristics of thawed sperm, the samples from different individuals were divided into HF (High Freezers, n=8) and LF (Low Freezers, n=8), and the lipidomic method based on UHPLC-MS/MS was used to correlate the semen quality of the thawed goats with the sperm lipidome, and the sperm with different cryotolerance, were identified by principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). The results showed that thawed goat sperm was rich in lipid subclass molecules such as phosphatidylcholine, phosphatidylethanolamine, triglycerides, ceramides, sphingomyelins. Comparative analysis showed that HF sperm had higher total lipid content, and the abundance of phosphatidylcholine and triglyceride was significantly higher than that of LF sperm, which may be due to the fact that HF sperm were able to take up more lipids in the freezing extender and have active lipid anabolic processes.